Aerobic, Anaerobic, Fungal, and Antimicrobial Sensitivity Patterns in CSOM Patients - Rahman, Nico Chairuar; Zahara, Devira; Rambe, Andrina Yunita Murni; Asroel, Harry Agustaf; Farhat, Farhat (Jurnal Biologi Tropis, 2026)
Chronic Suppurative Otitis Media (CSOM) remains a major global health problem, particularly in low- and middle-income populations. Variations in microbial etiology and antimicrobial susceptibility patterns necessitate periodic evaluation to support appropriate treatment. Objective: To describe the aerobic, anaerobic, and fungal microorganisms associated with CSOM and their antimicrobial susceptibility patterns. This descriptive cross-sectional study included 24 middle ear swab specimens collected from patients with CSOM. Specimens were transported using Amies agar transport medium and cultured on appropriate media. Microorganisms were identified through macroscopic and microscopic examinations and confirmed using the VITEK® 2 Compact system. Antimicrobial susceptibility testing was also performed. Most patients were male and presented with benign CSOM. Pseudomonas aeruginosa was the most common aerobic isolate (6 specimens). Fusobacterium necrophorum and Prevotella disiens were the predominant anaerobic bacteria, while Aspergillus spp. was the most frequently identified fungal pathogen in both benign and malignant CSOM. Amikacin and gentamicin showed the highest antimicrobial sensitivity among the bacterial isolates. Pseudomonas aeruginosa, Fusobacterium necrophorum, Prevotella disiens, and Aspergillus spp. were the predominant microorganisms identified in CSOM. The high sensitivity of amikacin and gentamicin supports their continued use as therapeutic options, guided by microbiological and susceptibility testing.